Administration of antineoplastic drugs and fecundity in female nurses. Issue 8 (20th June 2019) - Nassan, Feiby L.; Lawson, Christina C.; Gaskins, Audrey J.; Johnson, Candice Y.; Boiano, James M.; Rich‐Edwards, Janet W.; Chavarro, Jorge E.
Abstract: Background: We examined the association between the administration of antineoplastic drugs (AD) and fecundity among female nurses. Methods: AD administration and use of exposure controls (EC) such as gloves, gowns, and needleless systems were self‐reported at baseline among 2649 participants of the Nurses' Health Study 3, who were actively attempting pregnancy. Every 6 months thereafter, the nurses reported the current duration of their pregnancy attempt. Multivariable accelerated failure time models were used to estimate time ratios (TR) and 95% confidence intervals (CI) adjusted for age, race, body mass index, smoking, marital status, hours of work, and other occupational risk factors. Results: Mean (standard deviation) age and BMI at baseline were 30.7 years (4.7) and 26.0 kg/m 2 (6.4). Forty‐one percent of nurses reported ever administering AD; 30% only in the past and 11% currently. The former administration of AD (TR = 1.02, 95% CI, 0.93‐1.12) was unrelated to the ongoing duration of pregnancy attempt. Among nurses currently administering AD, those who had administered AD for 6 years and above had a 27% (95% CI, 6%‐53%) longer duration of pregnancy attempt than nurses who never handled ADs in unadjusted analyses. This difference disappeared in multivariable analyses (TR = 1.01, 95% CI, 0.85‐1.21). 93% ( n = 270) of the nurses currently administering ADs reported consistent use of EC. These nurses had a similar median duration of pregnancy attempt to those who never handled AD (TR = 1.00, 95% CI, 0.87‐1.15). Conclusions: Administration of ADs did not appear to have an impact on fecundity in a cohort of nurses planning for pregnancy with a high prevalence of consistent ECs. Our results may not be generalizable to women who are less compliant with PPE use or with less availability to ECs. Therefore, it is possible that we did not observe an association between occupational exposure to AD and reduced fecundity because of lower exposure due to the more prevalent use of effective ECs.